Inequalities and risk factors analysis in prevalence and management of hypertension in India and Nepal: a national and subnational study - Santosh Kumar Rauniyar; Md. Mizanur Rahman; Md. Shafiur Rahman; Sarah Krull Abe; Shuhei Nomura; Kenji Shibuya (BMC, 2020)
Abstract Background Hypertension is one of the leading risk factors for cardiovascular diseases in India and Nepal. Socio-economic disparity in these two countries has created wide gap in management of hypertension. However, inequalities in prevalence and management (awareness, treatment, and control) of hypertension is poorly assessed. This study analyzes the risk factors associated with prevalence and management of hypertension in India and Nepal and assesses the wealth-and education-based inequalities in them. Methods This study used data from the Demographic and Health Survey; a cross-sectional survey conducted between January 2015 to December 2016 in India and June 2016 to January 2017 in Nepal. A total of 787,713 individuals in India and 14,454 individuals in Nepal aged between 15 and 49 years were included in the study. Respondents were classified as being hypertensive if their systolic blood pressure (SBP) readings were at least 140 mmHg or diastolic blood pressure (DBP) readings were at least 90 mmHg, or if they reported currently taking anti-hypertensive medication. Multilevel logistic regression models with random intercepts at household-and community-levels were used to identify the risk factors associated with prevalence and management of hypertension. For inequality assessment, slope index and relative index of inequalities in prevalence and management of hypertension were estimated. Results Overall prevalence of hypertension in India and Nepal were 11.4% (95% confidence interval (CI), 11.4-11.5) and 19.6% (95% CI, 18.9-20.2), respectively. Less than one-third of the hypertensive population received treatment and below 20% among them had their blood pressure controlled. In both countries, wealth-and education-based inequalities in awareness, treatment, and control of hypertension were significantly high in urban and rural areas. Conclusion Wealth- and education-based inequalities in prevalence and management of hypertension were high among different socio-economic groups at national and sub-national levels. Tailored strategies are required to effectively manage hypertension in different regions by considering socio-economic and demographic factors.